Adoption costs of financial innovation: Evidence from Italian ATM Cards - Kim P. Huynh; Philipp Schmidt-Dengler; Gregor W. Smith; Angelika Welte (Bank of Canada, 2017)
The discrete choice to adopt a financial innovation affects a household's exposure to inflation and transactions costs. We model this adoption decision as being subject to an unobserved cost. Estimating the cost requires a dynamic structural model, to which we apply a conditional choice simulation estimator. A novel feature of our method is that preference parameters are estimated separately, from the Euler equations of a shoppingtime model, to aid statistical efficiency. We apply this method to study ATM card adoption in the Bank of Italy's Survey of Household Income and Wealth. There, the implicit adoption cost is too large to be consistent with standard models of rational choice, even when sorted by age, cohort, education or region.
Keywords: E41; D14; C35; 330; Bank notes; Econometric and statistical methods; Financial services